Difference between revisions of "009B Sample Midterm 3, Problem 3"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Compute the following integrals: ::<span class="exam">a) <math>\int x^2\sin (x^3) ~dx</math> ::<span class="exam">b) <math>\int_{-\frac{\pi}{4}}^{\frac{\...")
 
Line 1: Line 1:
 
<span class="exam"> Compute the following integrals:
 
<span class="exam"> Compute the following integrals:
  
::<span class="exam">a) <math>\int x^2\sin (x^3) ~dx</math>  
+
<span class="exam">(a) &nbsp; <math>\int x^2\sin (x^3) ~dx</math>  
::<span class="exam">b) <math>\int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2(x)\sin (x)~dx</math>
+
 
 +
<span class="exam">(b) &nbsp; <math>\int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2(x)\sin (x)~dx</math>
  
  
Line 8: Line 9:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|How would you integrate <math style="vertical-align: -5px">2x(x^2+1)^3~dx?</math>
+
|How would you integrate &nbsp;<math style="vertical-align: -5px">2x(x^2+1)^3~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -3px">u=x^2+1.</math> Then, <math style="vertical-align: -1px">du=2x~dx.</math> Thus,
+
&nbsp; &nbsp; &nbsp; &nbsp; You could use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -3px">u=x^2+1.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math style="vertical-align: -1px">du=2x~dx.</math>  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Thus,
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp;&nbsp;&nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int 2x(x^2+1)^3~dx} & = & \displaystyle{\int u^3~du}\\
 
\displaystyle{\int 2x(x^2+1)^3~dx} & = & \displaystyle{\int u^3~du}\\
 
&&\\
 
&&\\
Line 22: Line 29:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 29: Line 37:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -1px">u=x^3.</math> Then, <math style="vertical-align: -1px">du=3x^2~dx</math> and <math style="vertical-align: -14px">\frac{du}{3}=x^2~dx.</math>
+
|We proceed using &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -1px">u=x^3.</math>  
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -1px">du=3x^2~dx</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{3}=x^2~dx.</math>
 
|-
 
|-
 
|Therefore, we have
 
|Therefore, we have
 
|-
 
|-
 
|
 
|
::<math>\int x^2\sin (x^3) ~dx=\int \frac{\sin(u)}{3}~du.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\int x^2\sin (x^3) ~dx=\int \frac{\sin(u)}{3}~du.</math>
 
|}
 
|}
  
Line 43: Line 55:
 
|-
 
|-
 
|
 
|
::::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
\displaystyle{\int x^2\sin (x^3) ~dx} & = & \displaystyle{\frac{-1}{3}\cos(u)+C}\\
+
\displaystyle{\int x^2\sin (x^3) ~dx} & = & \displaystyle{-\frac{1}{3}\cos(u)+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{-1}{3}\cos(x^3)+C.}\\
+
& = & \displaystyle{-\frac{1}{3}\cos(x^3)+C.}\\
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 54: Line 66:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Again, we proceed using u substitution. Let <math style="vertical-align: -5px">u=\cos(x).</math> Then, <math style="vertical-align: -5px">du=-\sin(x)~dx.</math>  
+
|We proceed using u substitution.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: -5px">u=\cos(x).</math>  
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -5px">du=-\sin(x)~dx.</math>  
 
|-
 
|-
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|-
 
|-
|We have <math style="vertical-align: -15px">u_1=\cos\bigg(-\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math> and <math style="vertical-align: -15px">u_2=\cos\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}.</math>
+
|We have  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -15px">u_1=\cos\bigg(-\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math>&nbsp; and &nbsp;<math style="vertical-align: -15px">u_2=\cos\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}.</math>
 
|}
 
|}
  
Line 64: Line 82:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|So, we get  
+
|Therefore, we get  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2(x)\sin (x)~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^{\frac{\sqrt{2}}{2}} -u^2~du}\\
 
\displaystyle{\int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2(x)\sin (x)~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^{\frac{\sqrt{2}}{2}} -u^2~du}\\
 
&&\\
 
&&\\
Line 75: Line 93:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; '''(a)''' <math>\frac{-1}{3}\cos(x^3)+C</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>-\frac{1}{3}\cos(x^3)+C</math>
 
|-
 
|-
|&nbsp;&nbsp; '''(b)''' <math>0</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math>0</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:20, 9 April 2017

Compute the following integrals:

(a)  

(b)  


Foundations:  
How would you integrate  

        You could use  -substitution.

        Let  
        Then,  
        Thus,

     


Solution:

(a)

Step 1:  
We proceed using  -substitution.
Let  
Then,    and  
Therefore, we have

       

Step 2:  
We integrate to get

       

(b)

Step 1:  
We proceed using u substitution.
Let  
Then,  
Since this is a definite integral, we need to change the bounds of integration.
We have
         and  
Step 2:  
Therefore, we get

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam